Draft proposal for the sustainable municipal management of the surf tourism product in the municipality of Aljezur - Carrasco, Paulo (2017)
Sustainability is a general principle of public tourism policies in Portugal and is a fundamental principle for development, recommended by general and sectoral international organizations, such as the European Union and the World Tourism Organization. Surfing is a human recreational, sporting and formative activity that can contribute to the recognition of Aljezur as a national and international tourist destination and also provide a significant development opportunity for its community.